Penerapan Bimbingan Tesis Berbasis Lesson Study terhadap Percepatan Penyelesaian Studi Mahasiswa dalam Menerapkan Model Problem Based Learning (PBL) - Suciati Suciati; Widha Sunarno; Sarwanto Sarwanto (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
This study aims to determine the impact of the thesis guidance based lesson study (LS) to: 1) the acceleration of the student's accomplishment in Science Graduate Education Program UNS; and 2) the applicability of the implementation of problem based learning model. The method used in tne research was qualitative-descriptive. The population is all students of Semester 3rd in the Academic Year  2012/2013 at  Postgraduate Science Education Program UNS. Samples were selected by purposive sampling as researchers’ guidance student (M) which included 4 students with the different background and occupation, namely: 1) M.1: undergraduate student  of biology education and working as a teacher at SMP Negeri Surakarta with 10 years of teaching experience; 2) M.2: undergraduate student of  biology education and working as a private high school teacher in Surakarta with 13 years of teaching experience; 3) M.3: undergraduate student of biology education is a fresh graduate and have not been taught; 4) M.4: undergraduate student of natural biology and working as a lecturer at the Academy of Private Nursing in Surakarta. Descriptive qualitative methods are used to seeing the impact of the use of the guidance of a thesis-based lesson study to accelerating student study completion. The data collection technique is a technique test and non-test using a questionnaire, observation and documentation. Furthermore, the data were analyzed descriptively qualitative and presented in tabular form. The results showed: 1) Guidance LS-based thesis has an effective effect on the acceleration of the completion of studies students at UNS Graduate Science Education Program at (22.2%); and 2) Guidance based thesis can reduce students’ difficulties in research so that the problem based learning model can be implemented fluently.